2022
DOI: 10.3389/fphar.2022.829660
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of the “4+7” pilot policy on the volume, expenditures, and daily cost of Serotonin-Specific Reuptake Inhibitors (SSRIs) antidepressants: A quasi-experimental study

Abstract: Objectives: The purpose of this study was to quantitatively evaluate the impacts of the”4 + 7” pilot policy on purchase volume, purchase expenditures, and daily cost and to find the changes in the use of SSRIs.Methods: Data was collected covering 31 months, before, during, and after the “4 + 7” pilot policy was implemented in Shenzhen. Interrupted time-series (ITS) analysis was used to examine whether there had been a significant effect with the onset of the “4 + 7” pilot policy in March 2019.Findings: The dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…At the same time, the expenditure of the generic targeted anti-tumor drugs decreased(-81.64%, -43.45%, and − 93.10%), and the DDDc decreased(-85.54%, -85.86%, and − 84.93%), which met the requirements of the NCDP to reduce medicines cost and alleviate the drug burden of patients, which was similar to the results of previous studies [22,23]. Furthermore, a signi cant decrease in both the quantity and dosage of original targeted drugs employed was observed subsequent to the policy intervention, aligning with the ndings reported by Yang et al [7,[10][11][12].…”
Section: Drug Utilizationsupporting
confidence: 88%
See 1 more Smart Citation
“…At the same time, the expenditure of the generic targeted anti-tumor drugs decreased(-81.64%, -43.45%, and − 93.10%), and the DDDc decreased(-85.54%, -85.86%, and − 84.93%), which met the requirements of the NCDP to reduce medicines cost and alleviate the drug burden of patients, which was similar to the results of previous studies [22,23]. Furthermore, a signi cant decrease in both the quantity and dosage of original targeted drugs employed was observed subsequent to the policy intervention, aligning with the ndings reported by Yang et al [7,[10][11][12].…”
Section: Drug Utilizationsupporting
confidence: 88%
“…Previous studies have indicated that the volume of policy-related antiviral drugs, antidepressants, antihypertensives and antibiotics has a signi cant increase, while volume of related original drugs medications decreased sharply ,after implementing the NCDP in China. [7,[10][11][12]. At the same time, the NCDP policy has successfully reduced the drug expenditure of policy-relevant varieties [13].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al ( 31 ) showed that the implementation of the “4 + 7” policy increased the use of cardiovascular generic drugs and significantly improved access to affordable drug costs for patients. Wen et al ( 32 ) showed that batch procurement successfully reduced the price of selective serotonin reuptake inhibitors and improved access to affordable drugs, especially for patients with chronic diseases. Since its implementation, NVBP has successfully reshaped the Chinese drug market structure, making it more conducive to high-quality and low-cost generic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The fast rise of pharmaceutical expenditure and the resulting increase in total health expenses have brought a heavy burden to the finances and the daily medical care of the people around the world, accessibility and affordability of medicines have become major issues for healthcare systems globally (Seidman and Atun, 2017;Long et al, 2022;Wen et al, 2022;Zhang et al, 2022). And China is no exception (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%